1975
DOI: 10.2307/2401730
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Growth of Salvinia molesta (S. Auriculata Auct.) in Laboratory and Natural Conditions

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…Nasturtium biomass increased along a gradient of nutrient concentrations, with seedlings attaining the greatest biomass in the three highest nutrient treatments. The production of Nasturtium biomass observed in this study is consistent with that reported for several other species of nuisance aquatic plants grown under high nutrient concentrations, including Eichhornia crassipes and S. molesta (Mitchell & Tur, 1975;Reddy et al, 1989;Crossley et al, 2002;Xie et al, 2004). For example, E. crassipes biomass increased along a gradient from 0.5 to 5 mg l -1 N (approximately 357.1 to 3571 lm N) after which biomass did not respond to further increases in nitrogen (Reddy et al, 1989), which suggests that maximum growth rates were achieved at nitrogen concentrations of less than 3571 lm N. Similarly, Nasturtium seedlings in our study did not respond to further increases in nutrient concentrations beyond 97.49 lm N:13.00 lm P, suggesting a critical nutrient range between 18.24 and 97.49 lm N at which plant growth is either optimized or becomes limited by another resource.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nasturtium biomass increased along a gradient of nutrient concentrations, with seedlings attaining the greatest biomass in the three highest nutrient treatments. The production of Nasturtium biomass observed in this study is consistent with that reported for several other species of nuisance aquatic plants grown under high nutrient concentrations, including Eichhornia crassipes and S. molesta (Mitchell & Tur, 1975;Reddy et al, 1989;Crossley et al, 2002;Xie et al, 2004). For example, E. crassipes biomass increased along a gradient from 0.5 to 5 mg l -1 N (approximately 357.1 to 3571 lm N) after which biomass did not respond to further increases in nitrogen (Reddy et al, 1989), which suggests that maximum growth rates were achieved at nitrogen concentrations of less than 3571 lm N. Similarly, Nasturtium seedlings in our study did not respond to further increases in nutrient concentrations beyond 97.49 lm N:13.00 lm P, suggesting a critical nutrient range between 18.24 and 97.49 lm N at which plant growth is either optimized or becomes limited by another resource.…”
Section: Discussionsupporting
confidence: 91%
“…) approach or exceed the rates of other aquatic species, including some nuisance species, such as Salvinia molesta (17.16% per day, Mitchell & Tur, 1975) and Elodea canadensis (0.045 g day -1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"High levels of biomass production and doubling in less than 4 days occurred in salvinia in solutions with N and P combinations varying from 2 to 20 mg NH 4 -N L -1 and from 2 to 10 mg PO 4 -P L -1 [65]. It was reported that in Lake Kariba, Zimbabwe, the ramets doubled in 8 to 17 days [28]. In nutrient poor conditions densities form as high as 2500 ramets m -2 .…”
Section: Factors Affecting Growthmentioning
confidence: 99%
“…The apical and axillary buds give rise to the new branches at each node. Salvinia molesta exhibits "three phenotypic growth forms" mainly depending on habitat, crowding, and nutrient availability [28,41].…”
mentioning
confidence: 99%